Analisa Karakteristik Tanah Timbunan Ditinjau dari Hubungan Gradasi Butiran Tanah dengan Nilai CBR Rendaman dan Tanpa Rendaman - Yan Juansyah (Rekayasa : Jurnal Ilmiah Fakultas Teknik Universitas Lampung, 2016)
The California bearing ratio (CBR) is a penetration test for evaluation of the mechanical strength of natural soil, subgrades and basecourses carriageway construction. The basic site test is per- formed by measuring the pressure required to penetrate soil or aggregate with a standard area. The measured pressure is then divided by the pressure required to achieve an equal penetration on a standard crushed rock material. The CBR test is described in ASTM Standards D1883-05 (for laboratory-prepared samples). CBR-value is used as an index of soil strength and bearing capac- ity. This value is broadly used and applied in design of the base and the sub-base material for pavement. CBR-test was conducted to characterize the strength and the bearing capacity of the nine studied soils from with nine place diference. experiments conducted in the laboratory of soil mechanics Malahayati university. The soil test done is physical, standard proctor and CBR Unsoaked. CBR value obtained was 9.33 % minimum value and a maximum value of 19%. CBR- values need to be interpreted in the context of the general relationship between the CBR values and the gradation of the soils. It can used in pavement or road and other applications.